Implementation of Multicultural Values in Islamic Religious Education Teaching Materials at SMAN 1 Nganjuk - Firmansyah , Firmansyah; Junaidi , Junaidi; Abdurakhmonovich , Yuldashev Azim (Al-Insyiroh: Jurnal Studi Keislaman, 2023)
Research This is field research with use approach qualitative case study for identify contained multicultural values in PAI and BK teaching materials . Besides that's the goal study This Also reveal How values mentioned implementedÂ to in learning in class. For this reason, this research leads to the documentation of learning tools for Islamic religious education and the data is analyzed using an interactive model from Miles and Huberman.. Results from study This is PAI textbook at SMA Negeri I Nganjuk normatively trying _ accommodate found multicultural values includes a) Attitude democracy b) Tolerance and c) Anti- violence. In contextÂ delivery mark Multicultural in class . PAI learning, Islamic religious education teachers at SMA 1 try to synergize these multicultural elements that are adapted to the material and learning objectives , so that in the learning process in the classroom a multicultural nuance grows Â